Tecnologia da produção de silagem de milho em sistemas de produção de leite - Carvalho, Igor Quirrenbach de (2013)
This study aimed to identify production systems and factors affecting silage quality, diet of the animals, production and milk quality. Samples of corn silage were collected in 108 silos from farms in the Parana State and were collected data about crop, silage process, and characteristics of silos, diets, production and milk quality. The silage losses were evaluated qualitatively for surficial deteriorated layer, discard of silage and effluent. The physical evaluations were natural matter density (NMD), dry matter density (DMD), dry matter content (DM) and particles size. The effluent losses were higher in silages with lower dry matter content. There were greater losses by layer deteriorated when silos were the surface type, without cover with soil and removal of silage was with scoop tractor. The highest discard of silage occurred when the silage was harvested by self-propelled machine, the particle size was larger and the density of the silage was lower. There was no relationship between silage losses and chemical composition of silage and diet as well as the production and milk quality. The DMD had positive relationship with the nutritional value of silage and milk production and negative with milk fat and solids. The DM content had positive relationship with the nutritional value of the silage and negative with milk fat and solids. The particle size had no effect on the nutritional value of the silage, diet, milk production and quality. Farms that invest more in silage production have better silage quality and produce more milk.